Worldwide variations in EGFR somatic mutations: a challenge for personalized medicine - Lamy Pierre-Jean; Jacot William (BMC, 2012)
Abstract Two studies recently reported around 10% of EGFR activating mutations in triple negative breast cancers from Asian patients. However, we did not find any EGFR activating mutation in a series of 229 breast tumor samples from European patients. Like in lung cancer, the EGFR mutation profiles seem to be related to the ethnical origin of patients. This is an important point that should be considered when developing anti-EGFR therapies.